Enemy Alien Internment in Ontario’s Northland - Kordan, Bohdan (Ontario History)

(untitled) (The Ontario Historical Society, 2021)
Some 1,400 destitute aliens of enemy origin were put to work as prisoners of war (POWs) at Kapuskasing during the Great War, carving out of Ontario’s northland an experimental farm colony. Internment, which made this possible, however, highlighted the contradiction in their status as POWs. They were civilians after all. This contradiction helped create the conditions that exposed them to intemperate behaviour. Thus made vulnerable, the internees at Kapuskasing were compelled to work. Still others, considered “undesirable,” were held until deported at war’s end. Used and abused, unwelcomed and unwanted, their predicament reflected the general circumstances of internment, but also the unique role that Kapuskasing would play in Canada’s first national internment operations.